Extending the application of biocatalysis to meet the challenges of drug development. (December 2018) - Devine, Paul; Howard, Roger; Kumar, Rajesh; Thompson, Matthew; Truppo, Matthew; Turner, Nicholas
Abstract The pharmaceutical industry, driven by an increasing need to deliver new and more effective medicines to patients, is increasingly turning to the use of engineered biocatalysts for both lead generation of active compounds and the sustainable manufacture of active pharmaceutical ingredients. Advances in enzyme discovery, high-throughput screening and protein engineering have substantially expanded the available biocatalysts, and consequently, many more synthetic transformations are now possible. Enzymes can be fine-tuned for practical applications with greater speed and likelihood of success than before, thereby leading to greater predictability and confidence when scaling up these processes. Coupled with a greater awareness of which reactions are suitable for biocatalysis (for example, biocatalytic retrosynthesis), new chemoenzymatic and multi-enzyme processes have been designed and applied to the synthesis of a range of important pharmaceutical target molecules. Increasingly, researchers are exploring opportunities for using immobilized biocatalysts in flow conditions. In this Review, we discuss some of the key drivers and scientific developments that are expanding the application of biocatalysis in the pharmaceutical industry and highlight potential future developments that likely will continue to increase the impact of biocatalysis in drug development. Engineered biocatalysts are increasingly being used for both the identification and manufacture of active pharmaceutical ingredients. Here, the authors review key developments that are expanding the use of biocatalysis in the pharmaceutical industry.